Caracterização morfológica e produtiva em variedades de palma forrageira - Amorim, Philipe Lima de (2011)
In order to evaluate morphological and productive varieties of forage cactus, we conducted an experiment in randomized block design with 24 treatments and four replications. The characteristics assessed related to the plant and cladodes were: number, weight, area and volume of cladodes primary, secondary, tertiary and quaternary, area index and total volume of cladodes, production of fresh and dry, plant height and width. We also determined the correlations between the length, width, thickness, area and volume with the weight of cladodes. For the number of cladodes, area index and total volume of cladodes observed higher values for cultivars of the genus Nopalea For the weight, area and volume of cladodes, observed higher values for cultivars of the genus Opuntia. For the production of fresh and dry matter, the highest values were observed in the varieties Negro Michoacan F7 and Tamazunchale V12, respectively. For plant height varieties of the genus Opuntia, were the ones with the highest values. The area and volume of cladodes were the characteristics that showed the highest correlations with the weight of the green cladodes. Varieties Negro Michoacan F7, V7 and Tamazunchale V12 are the most suitable for cultivation. To increase the production of biomass should prioritize increasing the volume and number of cladodes to Nopalea and varieties of the genus Opuntia, respectively